Implementación de la contabilidad al comercial blacio ordoñez, del cantón atahualpa, provincia de el oro, periodo, noviembre/diciembre 2015 - Loayza Feijoo, Janeth Katherine (2016)
The present investigation is based on the “ACCOUNTING IMPLEMENTATION OF BLACIO ORDOÑEZ STORE; THIS IS LOCATED IN ATAHUALPA, PROVINCE OF EL ORO. PERIOD, FROM NOVEMBER TO DECEMBER 2015. This was done for helping the owner of the business to have a suitable system. Thus, she could take control of each transaction which she does every day. During the implementation of this project, I applied and put into practice all the acquired knowledge during the entire professional career. This, allowed me to create a tool for the owner; then she could make the best decisions for having a good performance of the business. Thanks to the elaboration of accounting practice the set objectives were accomplished and done. The researcher started with the collection of source documentation to create the initial inventory. Then, a plan and manual accounting for the business were done. The record of transactions in the journal for the movement of Account inventory was performed using a permanent Account System; the Kárdex cards were created to take control of the inventory. A balance test was performed, in the same way a worksheet was developed to conclude with the Financial Statements to know the true financial position of the Company. As a result, the researcher concludes that the implementation of accounting system will benefit the owner of business to organize all daily transactions and have it for the time she requires any information. Thus, she could perform and accomplish with all of her tax obligations. In addition, with the obtained results the recommendations and conclusions are presented.